EDUCATION OF THE DISABLED PERSON AND THE CHALLENGE OF INCLUSIVE SOCIETY (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
Building an inclusive society is a process of fundamental importance for development. Social, cultural and individual differences are used to enrich interactions and learning between human beings. It is a profound change in the behavior of a society. In Brazil, in the seventeenth and eighteenth centuries, discrimination and rejection were notorious, leading people with special needs to social exclusion, forcing families to hide them in asylums, prisons, or even at home. The National Policy of Special Education in the Inclusive Education Perspective 01/2008 proposes the change of values, attitudes and educational practices to meet all students, without any kind of discrimination, ensuring quality in education.